Irrational drug use and gastro-duodenal ulcerationsin a 3-month-old infant: A case report - Anwar, Saba; Narayani K, Vani; Deswal, Shivani; Dewan, Vivek (Indian Journal of Case Reports, 2019)
Upper gastrointestinal bleed (UGIB) is an unusual but potentially life-threatening emergency in children. Irrational use of medicines is one of most common cause. We, herein report a case of a three-month-old male child who presented with massive hematemesis and melena, probably due to the use of multiple antibiotics and analgesic use. On upper gastrointestinal endoscopy, multiple diffuse gastric and duodenal ulcers were detected. He was treated with proton pump inhibitors (PPI) and recovered completely within seven days.